Pengaruh Pemanfaatan Teknologi dan Motivasi terhadap Kinerja Pegawai Badan Balai Karantina Pertanian (BBKP) Makassar - Ferdinandus Ferdinandus; Rina Rina; Rahmi Usman (Jurnal Riset dan Inovasi Manajemen, 2023)
The aim of this research is to understand how the use of technology and motivation influences the performance of employees at the Makassar Agricultural Quarantine Agency (BBKP). This data was surveyed to obtain primary data. The Slovin formula was used in this study, and a total of 37 people were sampled. The validity and reliability of these findings have been evaluated, through tests of heteroscedasticity, multicollinearity, and normality have all been considered. The data analysis method uses multiple regression.